Peningkatan Minat Ibu Hamil Memberikan ASI Eksklusif melalui Promosi ASI Eksklusif: Increasing Interest of Pregnant Women in Providing Exclusive Breastfeeding through Promotion of Exclusive Breastfeeding - Taqwin Taqwin; Linda Linda; Nur Ifda (Jurnal Bidan Cerdas, 2022)
Introduction: The coverage of exclusive breastfeeding at the Mayoa Health Center is still low (56.2%) compared to the national coverage (66.1%), Central Sulawesi (61.9%) and Poso District (57.2%). The purpose of the study was to analyze the effect of exclusive breastfeeding promotion on the interest of pregnant women in giving exclusive breastfeeding. Methods: This type of research is pre-experimental with a pre-post group design. The research was carried out from 4-30 June 2021 in the working area of ​​the Mayoa Health Center, Poso Regency. The research sample was 48 respondents. Data collection before and after was carried out in the pregnant women class in each village using an interest questionnaire. Data that has been measured before the intervention. Exclusive breastfeeding promotion intervention was carried out by giving explanations to respondents through the MCH handbook. Post data was measured after the intervention. Data analysis in the form of frequency distribution and Wilcoxon test. Results: The results showed that all responses experienced an increase in interest in exclusive breastfeeding before the promotion of exclusive breastfeeding. Wilcoxon test results show the value = 0.000 <0.05. Conclusion: Promotion of exclusive breastfeeding increases the interest of pregnant women in providing exclusive breastfeeding in the working area of ​​the Mayoa Health Center. It is recommended to all midwives to promote exclusive breastfeeding with the MCH book in all classes of pregnant women intensively. The mother's interest in exclusive breastfeeding is followed up so that the baby gets exclusive breastfeeding.     ABSTRAK Pendahuluan: Cakupan ASI eksklusif di Puskesmas Mayoa masih rendah (56,2%) dibandingkan dengan cakupan nasional (66,1%), Sulawesi Tengah (61,9%) dan Kabupaten Poso (57,2%). Tujuan penelitian adalah menganalisis pengaruh promosi ASI Eksklusif terhadap minat ibu hamil dalam memberikan ASI Eksklusif. Metode: Jenis penelitian adalah pre eksperimental dengan pre post group design. Penelitian dilaksanakan mulai 4-30 Juni 2021 di wilayah kerja Puskesmas Mayoa Kabupaten Poso. Sampel penelitian sebanyak 48 responden. Pengumpulan data pre dan post dilakukan pada kelas Ibu Hamil pada masing masing desa dengan mengunakan kuesioner minat. Data pre diukur sebelum dilakukan intervensi. Intervensi promosi ASI eksklusif dilakukan dengan memberi penjelasan kepada responden melalui buku KIA. Data post diukur setelah dilakukan intervensi. Analisis data dalam bentuk distribusi frekuensi dan uji Wilcoxon. Hasil: Hasil penelitian menunjukkan bahwa seluruh respoden mengalami peningkatan minat memberikan ASI eksklusif sesudah diberikan promosi ASI eksklusif. Hasil uji Wilcoxon menunjukkan nilai ρ=0,000 <0,05. Kesimpulan: Promosi asi eksklusif meningkatan minat ibu hamil memberikan asi eklklusif di wilayah kerja Puskesmas Mayoa. Disarankan kepada seluruh bidan agar melakukan promosi ASI eksklusif dengan buku KIA pada semua kelas ibu hamil secara intensif. Minat ibu dalam memberikan ASI eksklusif ditindaklanjuti agar bayi mendapatkan ASI eksklusif.